2019
DOI: 10.7717/peerj.6375
|View full text |Cite
|
Sign up to set email alerts
|

Identification of special key genes for alcohol-related hepatocellular carcinoma through bioinformatic analysis

Abstract: BackgroundAlcohol-related hepatocellular carcinoma (HCC) was reported to be diagnosed at a later stage, but the mechanism was unknown. This study aimed to identify special key genes (SKGs) during alcohol-related HCC development and progression.MethodsThe mRNA data of 369 HCC patients and the clinical information were downloaded from the Cancer Genome Atlas project (TCGA). The 310 patients with certain HCC-related risk factors were included for analysis and divided into seven groups according to the risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
1
18
0
1
Order By: Relevance
“…UROC1 (p = 1.4E-3) encodes enzyme involved in histidine catabolism, metabolizing urocanic acid to formiminoglutamic acid. Zhang et al showed that UROC1 may play important roles in HCC development, especially alcohol-related HCC development and progression [52].…”
Section: Discussionmentioning
confidence: 99%
“…UROC1 (p = 1.4E-3) encodes enzyme involved in histidine catabolism, metabolizing urocanic acid to formiminoglutamic acid. Zhang et al showed that UROC1 may play important roles in HCC development, especially alcohol-related HCC development and progression [52].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent SVs in CSMD1, WWOX, ERC1, PDE4D and SHANK2 were also identified in five tumor samples. The CUB and Sushi multiple domains 1 (CSMD1) is a tumor suppressor gene reported to be associated with poor prognosis in many cancer types including breast cancer, gastric cancer, head and neck squamous cell carcinoma (HNSCC), and hepatocellular carcinoma (Deng et al, 2012) , (Zhang et al, 2019) , (Jung et al, 2018). Deletion of WWOX, a tumor suppressor gene, is frequent in esophageal adenocarcinoma (32%) and stomach adenocarcinoma (30.2%) and also observed in other human cancer types such as colon adenocarcinoma, bladder urothelial carcinoma and lung adenocarcinoma (Hussain et al, 2019).…”
Section: Structural Variations In Esccmentioning
confidence: 99%
“…It was reported that mutations in TRET promoter, CTNNB1, ARID1A are more common in alcohol-related HCC incidences 26. A recent study identified 5 up-regulated genes (CSMD1, MAGEA3, MAGEA6, CSAG1, and CSAG3) and 4 down-regulated genes (CD5L,UROC1, IGF2, and SLC22A10) that were associated with alcohol-related HCC 27…”
Section: Etiology and Pathogenesismentioning
confidence: 99%